Barriers to Women Participation in Sports and Physical Activity in Southern Rajasthan - Bhargava, Deepti (Journal of Commerce and Trade, 2017)
Women in sport can shape women's capabilities as leaders especially in traditional male areas. Women's participation in sport can create a substantial contribution to social life and overall development. Sports for women represent a fast growing area in India and it can be used as tool to empower women. Recent trends show that the knowledge and awareness among female towards sport participation is increasing. But as compare to other country and per ration of male and female, there is need to increase participation of female in sport and physical activities. Females of all ages generally have lower physical activity participation rates than males. Increasing physical activity levels for females is important for health and mental wellbeing. This Paper proposes to examine the situation of woman sports statuses in Southern Rajasthan.There are many factors which become barriers in women participation in sports activities. This paper highlights the barriers to women in participation in sports and physical activities. The paper is attempted to examine which barrier create more hurdle for females participation. The paper objective is also to find out the overall opinion of women toward sports activity. Final the researchers try to give recommendation to increase or motivate the women participation in sports and physical activities. JEL Classification : I 20, I 21, J 16.